Analysis of Risk Factors Associated With Drooping Deformity After Lower Eyelid Reconstruction: A Newly Developed Drooping Index. Issue 6 (June 2020) - Abe, Yoshiro; Ishida, Soushi; Mineda, Kazuhide; Yamashita, Yutaro; Yoshimoto, Sho; Hashimoto, Ichiro
Abstract : Background: Lower eyelid reconstruction is challenging because of the risk of severe postreconstruction deformities of the lower eyelid, such as drooping, entropion, and ectropion. However, the risk factors for these postreconstruction deformities are unclear. The present study aimed to quantify the drooping deformity of the lower eyelid after reconstruction using a cheek rotation flap and to identify risk factors associated with postreconstruction deformities. Methods: Our study group included 28 patients who underwent full-thickness lower eyelid reconstruction using a cheek rotation flap for anterior lamella reconstruction. We developed the drooping index to classify postreconstruction outcomes as good (index <1.2), fair (index between 1.2 and 1.5), and poor (index >1.5). We identified risk factors for a drooping deformity using univariate analyses (Mann-Whitney U or Spearman rank correlation, depending on data distribution). Results: Overall, the drooping index ranged between 1.0 and 2.11, with an average value of 1.3. A good outcome was obtained in 11, a fair outcome in 12, and a poor outcome in 5 patients. Clinically severe ectropion was observed in five of the 17 patients in the fair and poor outcome groups, with four of these patients requiring revision surgery. Risk factors for postreconstruction drooping deformity included medial location of the tumor, resection involving more than 50% of the horizontal width of the lower eyelid, and dissection of subcutaneous tissue of the cheek extending below the zygomatic arch. Conclusions: A cheek rotation flap provides satisfactory outcomes for full-thickness reconstruction of the lower eyelid. Extension of dissection of subcutaneous tissue of the cheek below the zygomatic arch increases the risk of postsurgical drooping deformity. Our drooping index provides a quantitative measure of drooping deformity and is clinically useful to classify outcomes.